A reduced complexity zero-forcing beamformer design for multiuser MIMO systems - Li, Bin; Feng, Z.; Dam, H.; Cantoni, A. (Springer Verlag, 2017)
Zero-forcing beamforming under per-antenna power constraints is considered for rural applications. By exploring the structures of a deterministic line-of-sight channel matrix, some properties are found for the optimal weighting matrix. Particularly, some constraints can be removed from the original formulation. With these properties, a reduced complexity zero-forcing beamformer design is proposed. Numerical examples under several different scenarios are provided.